2007
DOI: 10.1177/000348940711600210
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic and Acoustic Effects of False Vocal Folds and Epiglottis in Excised Larynx Models

Abstract: The addition of the supraglottic laryngeal structures has a significant impact on both aerodynamic and acoustic characteristics of excised larynges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 8 publications
5
56
0
2
Order By: Relevance
“…Because of the linear correlation between these two parameters, as displayed in the top row of Fig. 3, which has also been reported by Alipour and colleagues, 28,30,32,40 flow leakage in the setup was ruled out for all three larynges. The control variable for the succeeding measurements was subglottal pressure P S , which was kept constant during each experimental run.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Because of the linear correlation between these two parameters, as displayed in the top row of Fig. 3, which has also been reported by Alipour and colleagues, 28,30,32,40 flow leakage in the setup was ruled out for all three larynges. The control variable for the succeeding measurements was subglottal pressure P S , which was kept constant during each experimental run.…”
Section: Discussionmentioning
confidence: 56%
“…In the context of vocal fold adduction, different studies reported similar systematic results for both definitions of glottal flow resistance, i.e., increased glottal adduction resulted in increased flow resistance. 30,32 However, when investigating the impact of the ventricular folds, different behaviors for R A and R B were reported: Whereas Alipour et al 40 found increased flow resistance R A in the presence of the ventricular folds compared with configurations without ventricular vocal folds, Zhang et al 43 reported a decrease of glottal flow resistance R B . In a later study, Zheng et al 42 showed that these different findings, for small flow rates, result from the different definitions of R A and R B .…”
Section: Discussionmentioning
confidence: 99%
“…This radiated vocal power (and the associated SPL of 80-90dB at a distance of 15-18cm from the larynx) is remarkable only because the fundamental frequency is so low. Large canine larynges have produced an SPL of 82dB at a similar distance, but only with at least twice the subglottal pressure and at least twice the fundamental frequency (Alipour et al, 2007). Considering an increase of 6dB per doubling of subglottal pressure and another increase of 6dB for doubling of F 0 (Titze and Sundberg, 1992), we would expect on the order of 100dB for the tiger compared with 82dB for the canine.…”
Section: Discussionmentioning
confidence: 95%
“…Tsai et al, 2008). It is likely that they are also involved in nonhuman primate phonation, in particular in high-amplitude screaming (van den Berg, 1955;Agarwal et al, 2003;Alipour et al, 2007).…”
Section: Introductionmentioning
confidence: 99%